Glass ceramic and preparation method thereof
The antibacterial layer is prepared by pretreatment of dilute acid solution and mixed molten salt ion exchange, which solves the problems of high cost and poor antibacterial performance when using silver ions in microcrystalline glass, and achieves lower cost and better antibacterial performance of microcrystalline glass.
Patent Information
- Application Number
- CN202411862577.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Microcrystalline glass has higher cost when using silver ions, and antibacterial agents that do not contain silver ions lead to poor antibacterial performance.
The microcrystalline glass is pretreated with dilute acid solution, and an antibacterial layer is prepared by ion exchange by mixing molten salt (mass ratio of copper salt, sodium salt and potassium salt is 5:45:50~20:40:40) to replace silver ions.
It significantly reduces the preparation cost of the antibacterial layer, improves the antibacterial properties of microcrystalline glass, and performs better in dry environments, maintaining the beautiful color of the product.
Smart Images

Figure CN119661093A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of microcrystalline glass, and in particular to microcrystalline glass and a preparation method thereof. Background Art
[0002] In recent years, glass-ceramics has become the cover material for new-generation mobile display products such as smartphones and tablets due to its excellent fracture toughness and hardness. However, while satisfying the mechanical properties of the product such as scratch resistance and bending resistance, the product's antibacterial safety performance cannot be ignored either.
[0003] Although the silver ion antibacterial layer prepared by the ion exchange method on the cover glass can achieve good antibacterial effect, its cost is relatively high, and the product will also have defects such as discoloration during later storage and use, affecting the product's antibacterial rate and transmittance. Copper, as an element in the same main group as silver, also has good antibacterial properties and is relatively low in cost. The patent with publication number CN108779024 A uses a multi-step ion exchange method to prepare copper ion and silver ion antibacterial layers in antibacterial chemically strengthened glass and its optimized manufacturing method, and proposes the use of copper ions as antibacterial agents, but it has not been able to completely replace silver ions.
[0004] Therefore, in order to overcome the high cost of silver ions as the antibacterial layer of microcrystalline glass and the poor antibacterial effect of microcrystalline glass when silver ions are not used as antibacterial agents, it is necessary to obtain a microcrystalline glass and a preparation method thereof that can completely replace silver ion antibacterial properties and has excellent antibacterial properties. Summary of the invention
[0005] The present invention provides a microcrystalline glass and a preparation method thereof, which solves the problems in the related art that the cost of using silver ions for antibacterial purposes in microcrystalline glass is relatively high and an antibacterial agent without silver ions as an antibacterial layer of microcrystalline glass has poor antibacterial performance.
[0006] The technical solution of the present invention is as follows: The present invention provides a method for preparing glass-ceramics, comprising the following steps: S1, soaking the glass-ceramics in a dilute acid solution, and drying to obtain pretreated glass-ceramics; S2, using mixed molten salt to perform ion exchange on the surface of the microcrystalline glass to prepare an antibacterial layer to obtain an antibacterial microcrystalline glass; The mixed molten salt includes copper salt, sodium salt and potassium salt; The mass ratio of the copper salt, the sodium salt and the potassium salt is 5:45:50 to 20:40:40.
[0007] As a further technical solution, the microcrystalline glass is composed of the following components in mass percentage: SiO2: 62%~72%, Al2O3: 12%~20%, Li2O: 2.5%~4%, Na2O: 0%~3%, K2O: 0%~1%, ZnO: 1%~2.5%, TiO2: 1%~4%, ZrO2: 0.5%~4%, Y2O3: 2%~6%, and CeO2: 0.5%~3%.
[0008] As a further technical solution, the method for preparing the microcrystalline glass comprises the following steps: A1. According to the components of glass-ceramics, raw materials are weighed and melted, clarified and homogenized, formed, and annealed to obtain basic glass; A2, performing microcrystallization treatment on the base glass to obtain microcrystal glass; The melting temperature is 1550-1650°C; the molding temperature is 1350-1400°C.
[0009] As a further technical solution, the nucleation temperature during the microcrystallization treatment is 600-700°C, the nucleation time is 1-4 hours, the crystallization temperature is 800-900°C, and the crystallization time is 4-10 hours.
[0010] As a further technical solution, the crystal phase of the microcrystalline glass includes one or more of β-quartz, β-eucryptite, and spodumene.
[0011] As a further technical solution, the grain diameter of the microcrystalline glass is 10~50nm.
[0012] In the present invention, microcrystallization heat treatment can precipitate a large amount of low expansion crystal phase in the base glass, thereby achieving the effect of low expansion. During the nucleation treatment, the base glass precipitates crystal nuclei. When the temperature is lower than 600°C or higher than 700°C, the crystal nuclei are not precipitated completely, and the expansion coefficient is greater than 30×10 -7 / ℃. During the crystallization treatment, the crystal nucleus grows into a complete crystal. When the crystallization temperature is less than 800℃, the crystal size is less than 10nm. When the temperature is higher than 900℃, ion exchange is difficult, the antibacterial effect decreases, and the antibacterial rate is less than 90%. Therefore, the nucleation temperature of the microcrystalline glass is controlled between 600~700℃, the nucleation time is 1~4h, the crystallization temperature is between 800~900℃, and the crystallization time is 4~10h.
[0013] As a further technical solution, the dilute acid solution includes acetic acid solution and / or hydrofluoric acid solution.
[0014] As a further technical solution, the volume concentration of the acetic acid solution is 2% to 8%; the volume concentration of the hydrofluoric acid solution is 0.1% to 6%; When the dilute acid solution includes acetic acid solution and hydrofluoric acid solution, step S1 is: soaking the microcrystalline glass in acetic acid solution for 0.5 to 2 hours, drying, and then soaking in hydrofluoric acid solution for 15 to 120 seconds, drying, to obtain pretreated microcrystalline glass.
[0015] In the present invention, immersion in acetic acid solution can effectively reduce the occurrence of flaky color change defects after ion exchange. When the volume concentration is lower than 2%, the occurrence rate of flaky color change defects is 20%, and in the volume concentration range of 2% to 8%, the occurrence rate of flaky color change defects is only 5%. Immersion in hydrofluoric acid solution can promote ion exchange reaction, but when the volume concentration is greater than 6%, glass corrosion will occur. Therefore, the volume concentration of hydrofluoric acid solution is 0.1% to 6%.
[0016] As a further technical solution, the copper salt includes cuprous chloride; the sodium salt includes sodium chloride; and the potassium salt includes potassium chloride.
[0017] As a further technical solution, the mass ratio of copper salt, sodium salt and potassium salt in the mixed molten salt is 5~7:45:50.
[0018] In the present invention, a monovalent copper salt is used as an antibacterial agent, which is stable in high-temperature use and still maintains its original color when the temperature exceeds 600°C, thereby ensuring that the product has a beautiful color. When copper is used as an antibacterial agent, copper ions can act on bacterial cell membranes and cause protein denaturation to achieve a bactericidal effect. Copper ions are prone to coloring in glass, making the glass appear blue-green or red. At the same time, cuprous chloride is used as an antibacterial agent to achieve a good antibacterial effect and effectively avoid the occurrence of coloring, so that the microcrystalline glass after ion exchange maintains its original color, and the antibacterial effect is better when tested in a dry environment. The monovalent copper ion antibacterial glass is stable at high temperatures and still maintains its original color when heated to more than 600°C.
[0019] As a further technical solution, the ion exchange temperature is 500°C to 700°C, and the time is 0.5 to 3 hours.
[0020] As a further technical solution, a cooling treatment is further performed after the microcrystallization treatment; the cooling is furnace cooling to below 200°C.
[0021] The working principle and beneficial effects of the present invention are: In the present invention, the mixed molten salt uses copper salt, sodium salt and potassium salt, and the mass ratio of copper salt, sodium salt and potassium salt is limited to 5:45:50~20:40:40. Copper salt is used as an antibacterial agent. In a dry environment, copper ion antibacterial glass has a better antibacterial effect than silver ion antibacterial glass. In addition, copper, as an essential trace element for the human body, is safer and healthier than silver ions. At the same time, the preparation cost of the copper ion antibacterial layer is lower. The microcrystalline glass is pretreated with a dilute acid solution, which effectively prevents the generation of block discoloration defects on the glass surface, significantly improves the antibacterial property of the microcrystalline glass, and also improves the yield rate; when the mass ratio of copper salt, sodium salt and potassium salt in the mixed molten salt is lower than 5:45:50~20:40:40, the antibacterial effect of the antibacterial microcrystalline glass is poor, and it will also affect the treatment effect of the dilute acid solution, and it is easy to produce flaky color change defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0023] Figure 1 This is the crystal phase diagram of the microcrystalline glass prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the following examples and comparative examples, the copper salt is cuprous chloride, the sodium salt is sodium chloride, and the potassium salt is potassium chloride.
[0026] Example 1 The method for preparing glass-ceramics comprises the following steps: S1. According to the components of the glass-ceramics, raw materials are weighed, melted, clarified and homogenized at 1580° C., cooled to 1400° C., formed and annealed to obtain basic glass; S2, performing microcrystallization treatment on the base glass, cooling it to below 200° C. with the furnace, and obtaining microcrystal glass; The nucleation temperature during microcrystallization treatment is 650°C, the nucleation time is 3h, the crystallization temperature is 800°C, and the crystallization time is 5h. S3, ultrasonically cleaning the glass-ceramics with deionized water, soaking it in an acetic acid solution, washing it with deionized water and drying it, soaking it in a hydrofluoric acid solution, washing it with deionized water again and drying it, to obtain a pretreated glass-ceramics; The volume concentration of the acetic acid solution is 4%, the volume concentration of the hydrofluoric acid solution is 1%, the immersion treatment time of the acetic acid solution is 1 hour, and the immersion treatment time of the hydrofluoric acid solution is 30 seconds. S4, using mixed molten salt to perform ion exchange on the surface of microcrystalline glass at 500°C for 1h to prepare an antibacterial layer to obtain antibacterial microcrystalline glass; the mass ratio of copper salt, sodium salt and potassium salt is 5:45:50; The microcrystalline glass is composed of the following components in mass percentage: SiO2: 63%, Al2O3: 20%, Li2O: 2.5%, Na2O: 1.5%, K2O: 1%, ZnO: 2.5%, TiO2: 4%, ZrO2: 0.5%, Y2O3: 2%, and CeO2: 3%.
[0027] Example 2 The method for preparing glass-ceramics comprises the following steps: S1. According to the components of the glass-ceramics, raw materials are weighed, melted at 1600° C., clarified and homogenized, cooled to 1380° C., formed, and annealed to obtain basic glass; S2, performing microcrystallization treatment on the base glass, cooling it to below 200° C. with the furnace, and obtaining microcrystal glass; The nucleation temperature during microcrystallization treatment is 700°C, the nucleation time is 3h, the crystallization temperature is 800°C, and the crystallization time is 6h. S3, ultrasonically cleaning the glass-ceramics with deionized water, soaking it in an acetic acid solution, washing it with deionized water and drying it, soaking it in a hydrofluoric acid solution, washing it with deionized water again and drying it, to obtain a pretreated glass-ceramics; The volume concentration of the acetic acid solution is 4%, the volume concentration of the hydrofluoric acid solution is 2%, the immersion treatment time of the acetic acid solution is 1 hour, and the immersion treatment time of the hydrofluoric acid solution is 30 seconds. S4, using mixed molten salt to exchange ions on the surface of microcrystalline glass at 560° C. for 2 h to prepare an antibacterial layer to obtain antibacterial microcrystalline glass; the mass ratio of copper salt, sodium salt and potassium salt is 5:45:50; The glass-ceramic is composed of the following components in mass percentage: SiO2: 65%, Al2O3: 19%, Li2O: 4%, Na2O: 1.5%, K2O: 1%, ZnO: 2%, TiO2: 1%, ZrO2: 3%, Y2O3: 3%, CeO2: 0.5%; The crystal phase of the prepared glass-ceramics was tested, and the results were as follows: Figure 1 As shown, the crystal phase of the glass-ceramics is β-spodumene phase.
[0028] Example 3 The method for preparing glass-ceramics comprises the following steps: S1. According to the composition of the glass-ceramics, raw materials are weighed, melted, clarified and homogenized at 1650° C., cooled to 1450° C., formed and annealed to obtain basic glass; S2, performing microcrystallization treatment on the base glass, cooling it to below 200° C. with the furnace, and obtaining microcrystal glass; The nucleation temperature during microcrystallization treatment is 700°C, the nucleation time is 3h, the crystallization temperature is 800°C, and the crystallization time is 6h. S3, ultrasonically cleaning the glass-ceramics with deionized water, soaking it in an acetic acid solution, washing it with deionized water and drying it, soaking it in a hydrofluoric acid solution, washing it with deionized water again and drying it, to obtain a pretreated glass-ceramics; The volume concentration of the acetic acid solution is 3%, the volume concentration of the hydrofluoric acid solution is 2%, the immersion treatment time of the acetic acid solution is 0.5 h, and the immersion treatment time of the hydrofluoric acid solution is 50 s. S4, using mixed molten salt to perform ion exchange on the surface of microcrystalline glass at 550° C. for 0.5 h to prepare an antibacterial layer to obtain antibacterial microcrystalline glass; the mass ratio of copper salt, sodium salt and potassium salt is 7:45:50; The microcrystalline glass is composed of the following components in mass percentage: SiO2: 63%, Al2O3: 20%, Li2O: 3%, Na2O: 2%, K2O: 0.5%, ZnO: 1.5%, TiO2: 3%, ZrO2: 1%, Y2O3: 4%, and CeO2: 2%.
[0029] Example 4 The only difference between this embodiment and embodiment 3 is that the microcrystalline glass is not treated with a hydrofluoric acid solution.
[0030] Example 5 The only difference between this embodiment and embodiment 3 is that the microcrystalline glass is not treated with acetic acid solution.
[0031] Example 6 The method for preparing glass-ceramics comprises the following steps: S1. According to the composition of the glass-ceramics, raw materials are weighed, melted, clarified and homogenized at 1650° C., cooled to 1350° C., formed and annealed to obtain basic glass; S2, performing microcrystallization treatment on the base glass, cooling it to below 200° C. with the furnace, and obtaining microcrystal glass; The nucleation temperature during microcrystallization treatment is 700°C, the nucleation time is 3h, the crystallization temperature is 800°C, and the crystallization time is 6h. S3, ultrasonically cleaning the glass-ceramics with deionized water, soaking it in a hydrofluoric acid solution, and then washing and drying it with deionized water again to obtain a pretreated glass-ceramics; The volume concentration of the hydrofluoric acid solution is 2%, and the immersion treatment time of the hydrofluoric acid solution is 50 seconds; S4, using mixed molten salt to perform ion exchange on the surface of microcrystalline glass at 600°C for 1h to prepare an antibacterial layer to obtain antibacterial microcrystalline glass; the mass ratio of copper salt, sodium salt and potassium salt is 10:40:50; The microcrystalline glass is composed of the following components in mass percentage: SiO2: 68%, Al2O3: 16%, Li2O: 3%, Na2O: 2%, K2O: 0.5%, ZnO: 1.5%, TiO2: 3%, ZrO2: 1%, Y2O3: 3%, and CeO2: 2%.
[0032] Example 7 The difference between this embodiment and embodiment 3 is that the glass-ceramics is composed of the following components in mass percentage: SiO2: 62%, Al2O3: 12%, Li2O: 3.5%, ZnO: 1%, TiO2: 1%, ZrO2: 4%, Y2O3: 6%, CeO2: 0.5%; The nucleation temperature during microcrystallization treatment was 600°C, the nucleation time was 4 h, the crystallization temperature was 900°C, and the crystallization time was 4 h; The volume concentration of the acetic acid solution is 2%; the volume concentration of the hydrofluoric acid solution is 0.1%, the immersion treatment time of the acetic acid solution is 2 hours, and the immersion treatment time of the hydrofluoric acid solution is 120 seconds.
[0033] Example 8 The difference between this embodiment and embodiment 3 is that the glass-ceramics is composed of the following components in mass percentage: SiO2: 62%, Al2O3: 20%, Li2O: 3%, Na2O: 3%, K2O: 0.5%, ZnO: 1.5%, TiO2: 3%, ZrO2: 1%, Y2O3: 4%, CeO2: 2%; The nucleation temperature during microcrystallization treatment was 700°C, the nucleation time was 1 h, the crystallization temperature was 800°C, and the crystallization time was 10 h; The volume concentration of the acetic acid solution is 8%; the volume concentration of the hydrofluoric acid solution is 6%, the immersion treatment time of the acetic acid solution is 0.5h, and the immersion treatment time of the hydrofluoric acid solution is 15s.
[0034] Example 9 The only difference between this embodiment and embodiment 3 is that the mass ratio of copper salt, sodium salt and potassium salt is 20:40:40.
[0035] Comparative Example 1 The method for preparing glass-ceramics comprises the following steps: S1. According to the components of the glass-ceramics, raw materials are weighed, melted at 1650° C., clarified and homogenized, cooled to 1350° C., formed, and annealed to obtain basic glass; S2, performing microcrystallization treatment on the base glass, cooling it to below 200° C. with the furnace, and obtaining microcrystal glass; The nucleation temperature during microcrystallization treatment is 700°C, the nucleation time is 3h, the crystallization temperature is 800°C, and the crystallization time is 6h. S3, ultrasonically cleaning the glass-ceramics with deionized water, soaking it in an acetic acid solution, washing it with deionized water and drying it, soaking it in a hydrofluoric acid solution, washing it with deionized water again and drying it, to obtain a pretreated glass-ceramics; The volume concentration of the acetic acid solution is 5%, the volume concentration of the hydrofluoric acid solution is 0.5%, the immersion treatment time of the acetic acid solution is 2 hours, and the immersion treatment time of the hydrofluoric acid solution is 100 seconds. S4, using mixed molten salt to perform ion exchange on the surface of microcrystalline glass at 700°C for 2.5h to prepare an antibacterial layer to obtain antibacterial microcrystalline glass; the mass ratio of copper salt, sodium salt and potassium salt is 1:59:40; The microcrystalline glass is composed of the following components in mass percentage: SiO2: 68%, Al2O3: 16%, Li2O: 3%, Na2O: 2%, K2O: 0.5%, ZnO: 1.5%, TiO2: 3%, ZrO2: 1%, Y2O3: 3%, and CeO2: 2%.
[0036] Comparative Example 2 The difference between this comparative example and comparative example 1 is that step S4 is: using mixed molten salt to perform ion exchange on the surface of microcrystalline glass at 550° C. for 1 hour to prepare an antibacterial layer to obtain antibacterial microcrystalline glass; the mass ratio of copper salt, sodium salt and potassium salt is 20:40:40.
[0037] Comparative Example 3 The method for preparing glass-ceramics comprises the following steps: S1. According to the composition of the glass-ceramics, raw materials are weighed, melted, clarified and homogenized at 1650° C., cooled to 1450° C., formed and annealed to obtain basic glass; S2, performing microcrystallization treatment on the base glass, cooling it to below 200° C. with the furnace, and obtaining microcrystal glass; The nucleation temperature during microcrystallization treatment is 700°C, the nucleation time is 3h, the crystallization temperature is 800°C, and the crystallization time is 6h. S3. An antibacterial layer is prepared on the surface of a microcrystalline glass by ion exchange at 600°C for 1h using a mixed molten salt, the microcrystalline glass is ultrasonically cleaned with deionized water, immersed in an acetic acid solution, washed and dried with deionized water, immersed in a hydrofluoric acid solution, washed and dried again with deionized water, and an antibacterial microcrystalline glass is obtained; wherein the mass ratio of copper salt, sodium salt and potassium salt is 8:22:70, the volume concentration of the acetic acid solution is 5%; the volume concentration of the hydrofluoric acid solution is 5%, the immersion treatment time of the acetic acid solution is 1h, and the immersion treatment time of the hydrofluoric acid solution is 30s; The microcrystalline glass is composed of the following components in mass percentage: SiO2: 68%, Al2O3: 16%, Li2O: 3%, Na2O: 2%, K2O: 0.5%, ZnO: 1.5%, TiO2: 3%, ZrO2: 1%, Y2O3: 3%, and CeO2: 2%.
[0038] Comparative Example 4 The only difference between this comparative example and Example 3 is that the microcrystalline glass is not immersed in the acetic acid solution and the hydrofluoric acid solution.
[0039] Comparative Example 5 The difference between this comparative example and Example 3 is that the mass ratio of copper salt, sodium salt and potassium salt is 1:59:40.
[0040] The antibacterial rates of the antibacterial glass-ceramics prepared in Examples 1 to 9 and Comparative Examples 1 to 5 were tested according to the method of standard JC / T 1054-2007. The results are shown in Table 1 below.
[0041] Table 1 Test results
[0042] Compared with comparative examples 1 to 5, the antibacterial rate of the antibacterial microcrystalline glass prepared in embodiments 1 to 9 is higher, indicating that the antibacterial property of the microcrystalline glass is significantly improved by pretreating the microcrystalline glass with a dilute acid solution and then preparing the antibacterial layer with a mixed molten salt ion exchange.
[0043] Compared with Comparative Example 5, the antibacterial microcrystalline glass obtained in Examples 3 and 9 has a higher antibacterial rate, indicating that the mixed molten salt uses copper salt, sodium salt and potassium salt, and the mass ratio of copper salt, sodium salt and potassium salt is 5:45:50~20:40:40, which significantly improves the antibacterial property of the microcrystalline glass.
[0044] Compared with Comparative Example 4, the antibacterial rate of the antibacterial glass-ceramics prepared in Examples 4 to 5 is higher, indicating that the antibacterial property of the glass-ceramics is improved by pretreating the glass-ceramics with a dilute acid solution.
[0045] Compared with Examples 4 to 5, Examples 1 to 3 sequentially use acetic acid solution and hydrofluoric acid solution to pretreat the microcrystalline glass, which effectively prevents the occurrence of block discoloration defects on the glass surface and further improves the antibacterial property of the microcrystalline glass.
[0046] Although the process of preparing the antibacterial layer and then treating with dilute acid in Comparative Example 3 can achieve certain antibacterial performance, since hydrofluoric acid has a certain dissolving effect on glass, the antibacterial layer will also be destroyed, resulting in poor performance in subsequent antibacterial durability tests.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing glass-ceramics, characterized in that: The following steps are involved: S1, soaking the glass-ceramics in a dilute acid solution, and drying to obtain pretreated glass-ceramics; S2, using mixed molten salt to perform ion exchange on the surface of the microcrystalline glass to prepare an antibacterial layer to obtain an antibacterial microcrystalline glass; The mixed molten salt includes copper salt, sodium salt and potassium salt; The mass ratio of the copper salt, the sodium salt and the potassium salt is 5:45:50 to 20:40:
40.
2. The method for preparing glass-ceramics according to claim 1, characterized in that: The microcrystalline glass is composed of the following components in mass percentage: SiO2: 62%~72%, Al2O3: 12%~20%, Li2O: 2.5%~4%, Na2O: 0%~3%, K2O: 0%~1%, ZnO: 1%~2.5%, TiO2: 1%~4%, ZrO2: 0.5%~4%, Y2O3: 2%~6%, and CeO2: 0.5%~3%.
3. The method for preparing glass-ceramics according to claim 2, characterized in that: The method for preparing the microcrystalline glass comprises the following steps: A1. According to the components of glass-ceramics, raw materials are weighed and melted, clarified and homogenized, formed, and annealed to obtain basic glass; A2, performing microcrystallization treatment on the base glass to obtain microcrystal glass; The melting temperature is 1550-1650°C; the molding temperature is 1350-1400°C.
4. The method for preparing glass-ceramics according to claim 3, characterized in that: The nucleation temperature during the microcrystallization treatment is 600-700° C., the nucleation time is 1-4 hours, the crystallization temperature is 800-900° C., and the crystallization time is 4-10 hours.
5. The method for preparing glass-ceramics according to claim 3, characterized in that: The crystal phase of the microcrystalline glass includes one or more of β-quartz, β-eucryptite, and spodumene.
6. The method for preparing glass-ceramics according to claim 3, characterized in that: The crystal grain diameter of the microcrystalline glass is 10-50 nm.
7. The method for preparing glass-ceramics according to claim 1, characterized in that: The dilute acid solution includes acetic acid solution and / or hydrofluoric acid solution.
8. The method for preparing glass-ceramics according to claim 7, characterized in that: The volume concentration of the acetic acid solution is 2% to 8%; the volume concentration of the hydrofluoric acid solution is 0.1% to 6%; When the dilute acid solution includes acetic acid solution and hydrofluoric acid solution, step S1 is: soaking the microcrystalline glass in acetic acid solution for 0.5 to 2 hours, drying, and then soaking in hydrofluoric acid solution for 15 to 120 seconds, drying, to obtain pretreated microcrystalline glass.
9. The method for preparing glass-ceramics according to claim 1, characterized in that: The ion exchange temperature is 500° C. to 700° C., and the time is 0.5 to 3 hours.
10. The method for preparing glass-ceramics according to claim 3, characterized in that: After the microcrystallization treatment, a cooling treatment is performed; the cooling is furnace cooling to below 200°C.
Citation Information
Patent Citations
Antimicrobial chemically strengthened glass and optimization method for the manufacture thereof
CN108779024A
Transparent microcrystalline glass, microcrystalline glass product and preparation method thereof
CN111099829A
Milky white jade antibacterial glass and preparation method thereof
CN111943504A
Antibacterial fused salt, glass and preparation method
CN112209634A
Antibacterial impact-resistant safety glass and preparation method thereof
CN114315170A